2022
DOI: 10.30797/madencilik.994264
|View full text |Cite
|
Sign up to set email alerts
|

A study on effect of modified calcite on filler retention and mechanical properties of fluting papers

Abstract: In this study, the use of modified calcite as a filler in fluting paper production was investigated and its effects on retention and some mechanical properties of the papers were determined. Ground calcium carbonate (GCC/calcite) and cationic starch were used for modification. Filler modification with alum effect of CPAM resulted in starch-calcite encapsulation. Produced modified calcite (MC) was used in fluting paper production at certain dosages as filler. Simultaneously, paper was made with unmodified calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In another literature starch was used to modify GCC filler and added it to wet-end of papermaking and showed that retention of filler, burst strength and breaking length all were improved. 34 But here in case of set A4, burst factor increased along with the ash content of the paper handsheets to 22.24 and 18% respectively when compared with set A1, A2, and A3. For tear factor, TEA index and tensile stiffness (shown in Figures 8, 9, and 10) similar trend was noticed as that in breaking length Figure 11 showed 2.66% elongation in set A4 as compared to other sets with an elongation value around 1.7%.…”
Section: Setsmentioning
confidence: 74%
“…In another literature starch was used to modify GCC filler and added it to wet-end of papermaking and showed that retention of filler, burst strength and breaking length all were improved. 34 But here in case of set A4, burst factor increased along with the ash content of the paper handsheets to 22.24 and 18% respectively when compared with set A1, A2, and A3. For tear factor, TEA index and tensile stiffness (shown in Figures 8, 9, and 10) similar trend was noticed as that in breaking length Figure 11 showed 2.66% elongation in set A4 as compared to other sets with an elongation value around 1.7%.…”
Section: Setsmentioning
confidence: 74%
“…Starch was used as a binder in the coating process because of its properties that make it ideal for this purpose. Starch has a high molecular weight and forms a gel when mixed with water, which helps in binding the coating pigments together and anchor them to the cellulosic fibers in the WTT paper. , This enhances the adhesion of the coating to the substrate and contributes to the overall performance of the coated WTT papers.…”
Section: Resultsmentioning
confidence: 99%
“…The need for alternative sources of fiber and more sustainable production methods is becoming increasingly pressing in light of the global fiber shortage. 1 This has been noted by various studies. 2−4 The use of fillers in paper production is becoming increasingly popular as papermakers look for alternative and cost-effective ways to reduce the cost of cellulose and fiber.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations